Who's afraid of a big Black Hole? - Cooter, Stephen (London : BBC, 2010)
Black holes are by definition invisible, and there is no scientific theory that can adequately explain them. Nevertheless, researchers are determined to unravel the mysteries of black holes in the hope of answering some of the universe's most pressing questions. This program spotlights the work of MIT's Max Tegmark and Shep Doeleman as well as of string field theorist Michio Kaku as it questions the relevance of Einstein's General Theory of Relativity to black holes, attempts to apply quantum mechanics to black holes, discusses the characteristics of supermassive black holes, relates black holes to the Big Bang, and illustrates attempts to find and image black holes.
Series producer, James van der Pool ; photography, Tom Hayward ; film editor, Simon Sykes ; editor, Andrew Cohen
Narrated by: Samuel West
dvd format
Keywords: Black holes (Astronomy).; Cosmology